Efficacy of passive ultrasonic irrigation in the removal of three different intracanal medicaments - An in-vitro study - Gangaraju Shakapuram; Mayuri Sailaja Pachalla; Anand Ramtheerth Karne; Sandeep Shiva; J Deepa; Supriya Kommineni (Wolters Kluwer Medknow Publications, 2021)
Background: A successful root canal treatment involves the elimination of microorganisms, and prevents them from reinfecting the root and/or peri-radicular tissues. This can be mainly achieved by efficient cleaning and shaping of the root canal system. Due to the complexity of the root canal morphology, hand and rotary files cannot clean areas such as the isthmuses and lateral canals. In such cases, effective irrigation and the use of intracanal medicaments are essential. Medicaments that are applied should be removed before obturation. Aim: To evaluate the efficacy of passive ultrasonic irrigation in the removal of three different intracanal medicaments - Triple antibiotic paste (TAP), Odontopaste, and Metapex using a stereomicroscope. Methodology: A total of 45 single-rooted human teeth were selected and decoronated. The root canals were shaped with ProTaper rotary files. The specimens were fixed in modified Eppendorf vials with silicone material. The roots were split longitudinally, and a standardized groove was prepared in the apical part. The teeth were randomly divided into three groups each containing 15 samples based on the intracanal medicament used: TAP, Odontopaste, and Metapex. The root halves were reassembled with sticky wax and remounted in the Eppendorf vial. Each specimen was irrigated with 3% NaOCl and agitated using a passive ultrasonic device. The root segments were disassembled. Digital images were obtained using a stereomicroscope. Results: The data were evaluated statistically using Kruskal-Wallis and Mann-Whitney U tests. There was a statistically significant difference in the remaining intracanal medicament score (P < 0.05). Conclusion: Odontopaste showed the least remaining amount score, whereas TAP and Metapex showed greater retention within the dentin.